Simultaneous Electrochemical Determination of Dopamine, Epinephrine and Uric Acid at Silver Doped Poly-L-Cysteine Film Electrode - Ma, Wei; Yao, Xue; Sun, Dengming (Asian Journal of Chemistry, 2013)
An electrochemical sensor based on silver doped poly-L-cysteine film (Ag-PLC) has been fabricated for simultaneous determination of dopamine, epinephrine and uric acid in the presence of ascorbic acid. Although bare GC electrode resolves the voltammetric signals of dopamine and epinephrine, it fails to resolve the signals of dopamine and uric acid in a mixture. However, the silver doped poly-L-cysteine film modified electrode not only separates the voltammetric signals of dopamine, epinephrine and uric acid with potential difference of 390 and 135 mV vs. Ag/AgCl between dopamine-epinephrine in cathodic peak potential and uric acid-(dopamine + epinephrine) in anodic peak potential, respectively, but also shows higher electrocatalytic activity towards dopamine, uric acid and epinephrine in the presence of high concentration of ascorbic acid. Under the optimized conditions, the electrochemical sensor exhibited linear responses for uric acid concentration over the range 5.00 × 10-6 to 5.00 × 10-5 mol L-1 and 5.00 × 10-5 to 2.50 × 10-4 mol L-1. The amperometric current response was also increased linearly with the increase of dopamine concentration in the range of 5.00 × 10-6 to 1.10 × 10-4 mol L-1. For epinephrine, the linear ranges were 5.00 × 10-6 to 3.00 × 10-5 mol L-1 and 3.00 × 10-5 to 1.10 × 10-4 mol L-1, respectively. The practical application for the present modified electrode was demonstrated by determining the concentration of dopamine, uric acid and epinephrine in human urine samples.